Nucleation effect of unmodified graphene nanoplatelets on PVDF/GNP film composites. (June 2017) - Bidsorkhi, Hossein Cheraghi; D'Aloia, Alessandro Giuseppe; De Bellis, Giovanni; Proietti, Alessandro; Rinaldi, Andrea; Fortunato, Marco; Ballirano, Paolo; Bracciale, Maria Paola; Santarelli, Maria Laura; Sarto, Maria Sabrina
Graphical abstract: Abstract: Development of polyvinylidene fluoride (PVDF) film composite filled with carbon-based nanomaterials is attracting considerable attention in engineering applications. Numerous studies focus on the enhancement of PVDF properties by adding chemically modified graphene oxide or functionalized carbon nanotubes, or by modifying the polymer chains. On the other hand, in this paper we investigate the nucleation effect of graphene nanoplatelets (GNPs) on morphology and structure of PVDF, without any chemical modification or functionalization either of the GNPs or of the polymer chains. Thus, we fabricate GNP-filled PVDF composite films by the solution casting method. Then, we investigate the effect of GNPs on composite porosity, crystallinity and polymer phases, with special emphasis on the formation of β -phase. To this purpose, the produced PVDF/GNP composite films are characterized through scanning electron microscopy and atomic force microscopy topographies, differential scanning calorimetry, X-ray powder diffraction and Fourier transform infrared spectroscopy. All these experimental characterizations show that GNPs uniformly dispersed in PVDF, without any modification or functionalization, influence significantly the polymer structure and porosity, enhancing the β -phase crystals formation. Finally, the electrical, mechanical and electromechanical properties of the produced PVDF/GNP composite films are characterized.